Peak power shaving in hybrid power supplied 5G base station - Lee Jia Woon; Gobbi Ramasamy; Siva Priya Thiagarajah (Bulletin of Electrical Engineering and Informatics, 2021)
The Information and Communication Technology sector consumes approximately 3% of the world’s electrical energy due to the exploding demand for internet service. The most energy-intensive part of cellular communications is the base station, which there are about four million of them deployed globally. As Fifth Generation (5G) wireless networks are introduced, the number of base stations will be growing in parallel with the data traffic which in turn will increase the energy consumption of  the base station to cater for the growing capacity. The high-power consumption and dynamic traffic demand overburden the base station and consequently reduce energy efficiency. In this paper, an energy-efficient hybrid power supply system for a 5G macro base station is proposed. It is analysed that with the solar energy working in conjunction with the conventional supply from the grid, the reduction of poor power quality is observed as the fluctuation of the demand is greatly decreased. The proposed model showed a reduction in the average grid power by 14.9%. Furthermore, the power supply showed peak power shaving of 5kW; thus, reducing the reliance on the grid as well as increased the energy-efficient of this hybrid power supply system.